Interactions of MinK and e-NOS gene polymorphisms appear to be inconsistent predictors of atrial fibrillation propensity, but long alleles of ESR1 promoter TA repeat may be a promising marker - Šmalcelj, Anton (Array, 2009)
Abstract: Interactions of MinK and e-NOS Gene Polymorphisms Appear to Be Inconsistent Predictors of Atrial Fibrillation Propensity, but Long Alleles of ESR1 Promoter TA Repeat May Be a Promising Marker. We analyzed minK, e-NOS and ESR1 gene polymorphisms in 40 patients with atrial fibrillation (AF) without major structural heart disease compared to 35 healthy controls. A missense polymorphism in the minK gene with A/G substitution at nucleotide 112 causing serine (S) to glycine (G) change, 786 T/C polymorphism in the 5’ flanking region of e-NOS gene and TA polymorphism in the regulatory region of estrogen receptor ESR1 gene with long (ł19 TA repeats) and short alleles were examined. Only a slight increase in minK G allele frequency, but with marked excess in AG/TT combination of minK and e-NOS polymorphisms was found in the AF group. The interpretation remains tentative due to small groups precluding statistical significance of differences, possible lab flaws and inconsistencies with earlier data. However, ESR1 long allele homozygotes were strikingly more frequent in the AF than in control group, reaching statistical significance surprisingly in males (p<0.02). Functional activity of estrogen receptors may be more critical in males than in females with abundance of circulating estrogen. Contrasting the intricate complexity of genetic polymorphisms influencing cardiac rhythm with our modest research, we would limit the conclusion to the plea for further research of ESR1 role in AF